2021
DOI: 10.3390/nu13113850
|View full text |Cite
|
Sign up to set email alerts
|

Eating Behaviors of Children with Autism—Pilot Study, Part II

Abstract: Autism spectrum disorder is characterized by social communication deficit and non-normative behavior. The people with autism often experience troubles with feeding. The purpose of this study was to conduct evaluation of the feeding and eating behaviors among children with autism. Patients and Methods: The study group included 41 high-functioning autistic children. The control group consisted of 34 children without the ASD. The questionnaire was used to assess the nutritional status. Results: The children with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 44 publications
1
2
0
1
Order By: Relevance
“…In the present study it was found that the presence of the following behaviors ( disrupt eating include leaving the dining table before finishing the meal, getting angry at mealtimes, and turning face or body away from the food) is consistent with the results of a study conducted by Kazek, et al (2021) (18) , which showed that children with autism spectrum disorder frequently make noise while eating, need entertainment and divert their attention, are fed by their parents, and eat their meals away from the table. (18) PISSN: 2974-3281 EISSN: 2974-329x…”
Section: Resultssupporting
confidence: 92%
“…In the present study it was found that the presence of the following behaviors ( disrupt eating include leaving the dining table before finishing the meal, getting angry at mealtimes, and turning face or body away from the food) is consistent with the results of a study conducted by Kazek, et al (2021) (18) , which showed that children with autism spectrum disorder frequently make noise while eating, need entertainment and divert their attention, are fed by their parents, and eat their meals away from the table. (18) PISSN: 2974-3281 EISSN: 2974-329x…”
Section: Resultssupporting
confidence: 92%
“…A literatura mostrou que crianças com autismo podem ter dificuldades em aceitar certas texturas, tendo como preferência os alimentos pastosos, também rejeitam mais os alimentos, são mais exigentes, reticentes ao novo e aceitam uma variedade restrita do que lhes é ofertado. Tais comportamentos podem ser prejudiciais para o desenvolvimento da criança, podendo causar inadequações nutricionais e prejuízos à saúde (DIAZ et al, 2021;LÓPEZ et al, 2021;KAZEK, 2021;ESPOSITO, 2023).…”
Section: Resultsunclassified
“…Although, changes to appetite during illness are not isolated to those with ASD, as most children that experience illness has been shown to have a reduced food intake by 15-20% whilst experiencing upper respiratory infections, diarrhoea, or fevers [19]. However, food selectivity has been shown to occur more frequently in children with ASD compared to those without [20], for which the biological basis largely remains unknown. Some studies have suggested atypical sensory stimulation to be the likely cause towards food selectivity [21,22].…”
Section: Discussionmentioning
confidence: 99%